Optimal design of a pair of vibration suppression devices for a multi‐storey building. Issue 3 (11th December 2019) - Zhang, Sara Ying; Neild, Simon; Jiang, Jason Zheng
Summary: This paper investigates the use of two two‐terminal vibration suppression devices in a building and assesses the performance benefits over those achieved using a single device. The inerter‐combined configurations for a multi‐storey building structure are considered. The inerter is a two‐terminal device, with the property that the applied force is proportional to the relative acceleration across its terminals. In this paper, a five‐storey building model with two absorbers of the same kind subjected to base excitation is studied, where one is located between ground and the first floor and the other is between the first and second floors of the building. Three passive suppression layouts, two dampers, two tuned inerter dampers, and two tuned viscous mass dampers are considered. The optimal configurations for minimising the maximum interstorey drifts of the building are obtained with respect to the inerter's size and the damping boundary. The corresponding parameter values are also presented. For the sake of comparison, the single device mounted between the ground and first floor is also considered. Finally, with specific inertance and damping values, the frequency response is provided to show the potential advantage of the proposed optimal configurations. It is demonstrated that the optimal configurations with a pair of devices are more effective than the optimal single device with equal total inertance and the same total damping boundary. The approach demonstrated in this paper is applicable to the investigation of using more than two devices for multistorey buildings.